What We Talk about When We Talk about ’Local’ Participation in International Biodiversity Law. The Changing Scope of Indigenous Peoples and Local Communities’ Participation under the Convention on Biological Diversity - Parks, Louisa; Schröder, Mika (PARTECIPAZIONE E CONFLITTO, 2019)
This article explores the meaning of participation by indigenous peoples and local communities’ in the Decisions of the Convention on Biological Diversity (CBD) from the perspectives of civic and radical environmentalism. The first sees participation as key for just and effective decision-making. Radical environmentalism argues instead for fundamental transformation to address environmental crisis. The article contributes to discussions about the importance of indigenous peoples and local communities for better and more just policies, or whether a more radical approach is necessary. The research uses empirical findings to deepen our understanding of ’local’ participation under the CBD and uncovers many meanings. Most describe mechanisms for participation, suggesting scope for civic environmentalism. Yet a closer look raises a range of questions, leading to suggestions for future action and research.